Composting of distillery spent wash - Borges Silva, Lara Rúbia; Kardos, Levente (Journal of Environmental Geography, 2023)
Distillery spent wash, a by-product of the alcoholic beverage industry, is an organic waste whose management poses significant challenges due to its acidity, high organic load, notable content of polyphenols, macronutrients, micronutrients and heavy metals. In Europe, billions of liters of distillery waste are generated annually and its eco-unfriendly disposal can cause severe environmental and health impacts. Composting is a viable management strategy to treat and manage distillery slop promoting the recycling and stabilization of organic matter and nutrients in the material. The review examines different composting methods, such as single composting, co-composting and vermicomposting, along with their benefits and drawbacks. To optimize composting effectiveness, various materials, such as sewage sludge, vinasse, green and animal manure, inorganic amendments, bagasse, filter cake and municipal solid waste, among other agro-food and animal bio-wastes, can be used as a source of nitrogen and microorganisms. Also, the usage of different materials and mixtures aims to enhance the composting process increasing the degradation rate and the quality of the compost. The challenges of distillery spent wash composting are also covered in the paper which are mainly due to its characteristics, including high salt content, low carbon-to-nitrogen ratio, low pH and potential phytotoxicity. The paper concludes that composting distillery spent wash is an effective and sustainable waste management solution for recovering valuable nutrient resources and producing a stable nutrient-rich organic soil amendment. The produced compost can improve crop yields, nutrient absorption by plants and plant biomass and contribute to soil properties and restoration. The review provides insights into the current state of distillery spent wash composting and recommends future research directions to improve efficiency and expand potential applications.